Presepsin level as risk factor for mortality in premature infants with neonatal sepsis - Muhammad Ifan Romli; Tetty Yuniati; Dany Hilmanto (Indonesian Pediatric Society, 2021)
Background Prematurity is a risk factor of neonatal sepsis and its associated morbidities and mortality. Most deaths in neonatal sepsis occur within the first seven days. Presepsin has been reported as one of the earliest biomarkers for predicting mortality. Objective To determine the association between presepsin levels and mortality risk, as well as the optimal presepsin cut-off point for predicting mortality, in premature infants with neonatal sepsis. Method This was an observational prospective cohort study on 62 preterm infants born at 28 to <37 weeks' gestation. We recorded clinical and laboratory characteristics, performed blood culture, and measured presepsin levels at initial diagnosis of sepsis. Subjects were followed for seven days and their outcome (death or survival) recorded. We evaluated the association between clinical and laboratory characteristics, including presepsin levels, with sepsis outcome. We also constructed a receiver-operator characteristics curve to determine the optimal cut-off point of presepsin as a predictor of sepsis mortality. Results Only blood culture results (P=0.006) and presepsin level (P<0.001) were significantly associated with sepsis outcome on the seventh day. The optimal presepsin cut-off value for predicting mortality was 1057 ng/mL, with an area under curve of 80.4%, sensitivity of 60.71%, and specificity of 88.24%. A presepsin level of >1057 ng/mL was associated with increased mortality [RR 3.02; 95%CI 68.3 to 89.4; P<0.001]. Conclusion In preterm infants with neonatal sepsis, an elevated presepsin level at diagnosis is a significant risk factor for mortality within seven days. Presepsin can be used as an early biomarker of sepsis outcome.